Spectrum cognitive intelligent management and control for aviation 6G - Dong LIU; Qihui WU; Quek Tony Q.S. (物联网学报)
With the development of the ground-air-space integrated information network,satellite networks and ground mobile networks serve as space and ground fundamental infrastructures,respectively.While various aerial platforms such as drones constitute air mobile networks to connect space and ground infrastructures.As an important form of 6G,aviation 6G will include new types of air-to-air,air-to-ground and air-to-space communication and networking techniques.An important issue for aviation 6G is how to efficiently use spectrum resources.Based on the challenges of aviation 6G and electromagnetic spectrum space,a spectrum cognitive intelligent management and control architecture for aviation 6G was proposed,and the functions were elaborated of the four main modules in the architecture,namely spectrum cloud,spectrum control link,device spectrum software defined and spectrum sensor network.Three key technologies of spectrum cognitive intelligent management and control for aviation 6G were analyzed and discussed,namely intelligent three-dimensional spectrum space digital twins,3D spectrum intelligent decision,and rapid collaborative learning of spectrum mapping.It is expected to provide guidance and suggestions for the subsequent research on aviation 6G and spectrum intelligent management and control.